POLYCYCLIC AROMATIC HYDROCARBON (PAHs) AND THEIR BIODEGRADATION BY BACTERIA - Minh, Nghiêm Ngọc (Vietnam Journal of Biotechnology, 2013)
Around the world and in Vietnam, with the development of society, the request for raw materials and fuel increases that bring about widenning exploiting, processing industries such as: petroleum industry, paint producing, wood producing, textile and dye industry or toxic detergent and chemicals processing, etc. The industrial activities release a large mount of  toxic waste, which pollute environment and influence human health. Beside some breakdown, the main reason of pollution is the waste that doesn’t strict treat or doesn’t treat and they discard the environment, to break though balance of ecology and cause serious effect to human health. Among them there are several PAHs that cause cancer and mutation, they alway exist in water, industrial wastes and petroleum. The complete degradation of PAHs from various sources requires a community of microrganisms. When PAHs are taken by microorganisms, they will be activated in aerobic metabolism by insertion of two oxygen atoms by bacteria and greenalgae to produce either cis-dihydrodiols or phenols. PAHs may also be activated by cytochrome P450 of many fungi and bacteria to produce arene oxides. This activation may also be performed by lignin degrading enzymes to produce quinies. In this review, we only focus on bacteria that degradate PAHs.